Aplikasi Konsep Personal Knowledge Management (PKM) dengan Social Web - Putri, Nuril Kusumawardhani Soeprapto (ComTech: Computer, Mathematics and Engineering Applications, 2012)
This study discusses the impact of social media to the development of personal knowledge management (PKM). Here the author describeS the factual condition of the company that useS social media as a means of personal knowledge management. Furthermore, these interaction patterns have significant impact on the organization. The purpose of this article is to analyze the application of personal knowledge managementconcept, combined with the social media concept that focuses on social networks with the consideration that they are widespreadly used by the public. Plus the emergence of social networking sites are increasingly new added value to the development of social media. The method used is literature study obtained from the online journals, articles and text books. The result of this study is expected to expand the use of social networking as a means of personal knowledge management in the organization.